Imigracja jako czynnik zmiany statusu i postrzegania Polski w zglobalizowanym świecie - Duszczyk, Maciej (Studia Socjologiczno-Polityczne. Seria Nowa, 2022)
The paper analyzes the migration processes that have taken place and are still taking place in Poland as a factor that can positively influence the perception of Poland in the world. Poland is an example of a country that very quickly changed its status from an emigration state to an immigration one. This is evidenced by the positive migration balance and the issuance of the largest number of temporary residence permits in the European Union. The status of an immigration state was confirmed by the influx of war refugees from Ukraine and numerous decisions to stay in Poland for a long time and permanently, as well as an attempt to open a new migration pathway running through the Polish-Belarusian border. It should be assumed that with appropriate conduct of foreign policy, this new situation in Poland can strengthen its international position and perception. At the same time, there are also risks associated with it. If there is a failure to respond properly and in accordance with the law and the rules of democratic states to the migration challenges, it could result in the entrenchment of negative opinions about Poland from the migration perspective that emerged during the migration crisis of 2015–2016.